The effect of an emollient with benfothiamine and Biolin prebiotic on the improvement of epidermal skin function - Narbutt, Joanna; Bednarski, Igor; Lesiak, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Complications of diabetes can damage internal organs and the skin. Diabetic skin, irritated and dry, is susceptible to skin infections. However little is known about influence of emollients on biophysical changes in skin during diabetes. Aim : To evaluate clinical skin changes after application of emollients with benfothiamine and Biolin prebiotic and to assess changes in biophysical parameters of the skin before and 4 weeks after daily application of an emollient. Material and methods : We recruited 50 patients with diabetes mellitus type 1 (DM1) or type 2 (DM2). All participants applied emollients on their left forearms and left shins for 4 weeks. The biophysical properties: pH, transepidermal water loss (TEWL), hydration of the stratum corneum and sebum content were measured and compared to those before enrollment to the study, after 1 h, 1 week and 4 weeks after application of an emollient. Results : After 4 weeks of treatment, there was an increase in skin hydration (40.61 ±19.03 vs. 48.83 ±15.51), pH (5.11 ±0.56 to 5.27 ±0.48) and sebum content (22.16 ±8.67 to 63.99 ±25.41) and a decrease in TEWL (12.54 ±5.6 vs. 9.85 ±5.69 g/m2/h) on forearms (p < 0.05 for all comparisons). On lower legs, significant changes in skin hydration (37.21 ±14.01 vs. 43.95 ±12.67), pH (5.04 ±0.57 to 5.31 ±0.49), sebum content (25.82 ±10.46 to 72.63 ±31.23) and TEWL (8.87 ±4.05 vs. 7.39 ±3.22 g/m2/h) were observed (p < 0.05 for all comparisons). Conclusions : Our study provides an insight into changes in diabetic skin after application of an emollient. To our knowledge, this is the first report on the emollient containing benfothiamine and Biolin prebiotic and its influence on biophysical parameters of epidermis.